Circular Creative Economy Incubation in Rural Citrus-Based Communities: A Case Study of the Gema Dewata Program in Indonesia - M. Maulana; Azam Asykarullah; Abdul Rachman Para Buana; Rama Sanjaya; Catherine Wahyuning Wilujeng (CV. Ulil Albab Corp, 2026)
This study examines how community-based creative-economy incubation can accelerate SDG-oriented rural transformation through circular value-chain upgrading. Using in-depth interviews with local actors, secondary document analysis, thematic interpretation, and value-chain mapping, the research found that the program transformed a vulnerable citrus monoculture into a three-tier circular creative-economy ecosystem. At the upstream level, adoption of a Trichoderma-based biofungicide through the BU JUSI subprogram increased citrus productivity from 3 to 5 tons per hectare (a 66.7% gain), reduced chemical fertilizer dependence by 20%, and stabilized the livelihoods of 320 farming households. At the meso level, BUDE ARTA MAJU converted substandard citrus yields into value-added food products, creating gender-inclusive microenterprise opportunities for rural women. At the downstream level, PAKLEK MANIS valorized 34.79 tons of citrus peel waste annually into bio-based commercial products (bioplastics, soap, bath salts, and aromatherapy items), potentially avoiding 36.525 tons of CO2e emissions per year. The study contributes to rural development, creative-economy, and circular-economy scholarship by proposing an integrated incubation model in which ecological restoration, value-added processing, women’s entrepreneurship, and waste valorization act as mutually reinforcing mechanisms. The findings suggest that CSR-driven rural empowerment can move beyond short-term aid when designed as a localized circular value-chain ecosystem that advances decent work, responsible production, and community resilience